Understanding the rule of prevalence in the NIS directive: C-ITS as a case study. Issue 40 (April 2021) - Ducuing, Charlotte
Abstract: The paper discusses the interpretation of the rule of prevalence of Article 1 (7) NIS Directive, which has not been the subject of any academic debate so far. Article 1 (7) NIS Directive organises the interface between the NIS Directive regime and other European Union sector-specific legislations imposing (cyber)security obligations, by laying down the conditions according to which such obligations would prevail over the NIS Directive regime. Based on the case study of the recent proposal from the European Commission to regulate Cooperative Intelligent Transport Systems ('C-ITS'), the paper unravels a number of issues and unclarities. Recommendations are made with respect to the interpretation and application of the rule of prevalence of Article 1 (7) NIS Directive. In anticipation of a potential future C-ITS regulation and in the context of a possible upcoming revision of the NIS Directive, the paper also makes suggestions to ease the regulation of the interface between the NIS Directive and other (cyber-)security regulation, particularly in the field of C-ITS.